Girls' education and sexual regulation in Malawi. Issue 4 (19th May 2022) - Silver, Rachel; Morley, Alyssa
ABSTRACT: Sexual regulation has been a core component of formal schooling in Southern Africa since its inception, with discipline central to teachers' work. Yet internationally funded, girl-focused development programs give new shape and legitimacy to teacher interventions on student sexuality. Building on a combined two years of multi-sited ethnographic research in Zomba, Malawi, we show how teachers and mother groups used NGO-sponsored activities to surveil and regulate girls. We argue that, as they implemented projects, school-based actors mediated between transnational logics about the power of girls' education and deeply historic understandings of schooling and girlhood. Teacher and mother group members remade programmatic components in ways that intensified discipline for some girls and ignored others. We theorize this differentiation as a pragmatic response to local socio-economic constraints and argue that, as a result, techno-rational programs designed to keep girls in school may instead push some out.